Peran Manajemen Sumberdaya Manusia dalam Meningkatkan Kinerja Karyawan di Kantor Unit BRI Modayag - Iwan H.P. Manoppo; Sicilya C. Mokoginta; Erna Manoppo; Jumie S. L. Mokoginta; Reza Apreliah Dg. Matara; Mohammad Afdal Mamonto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The role of human resource management (HRM) significantly influences the improvement of employee’ performance at BRI Unit Modayag. Effective HRM determines to what extend employees work and demonstrate competence in related fields. This study aims to determine the role of HRM in improving employee performance at BRI Unit Modayag. The type of this research is field research by using interview and documentation methods. The nature of this research is descriptive qualitative with inductive analysis. The results show that HRM significantly impacts the improvement of employee performance, it is proved by the increase in the number of customers. HRM implementation includes recruitment, selection, training, and compensation.